Liquidity reserves of Danish firms: Implications during the COVID-19 epidemic - Tobias Renkin (Danmarks Nationalbank, 2020)
We analyse the distribution of internal liquidity reserves among Danish firms during normal times. The median firm has reserves covering about one month of "fixed capacity cost". About a third of firms have reserves close to zero. We show that cost and wage compensation schemes, as implemented in Denmark during the current coronavirus epidemic, substantially extend the duration of liquidity reserves for firms with some reserves. Firms with very low reserves have to rely on external sources of liquidity.
Keywords: 330; Betriebliche Liquidität; Coronavirus; Lohnsubvention; Dänemark